Realtí virtuale nei Beni Culturali: Mersiva - Daniele Tomassucci (mediaGEO soc. coop., 2017)
Since 2010, Araundu brings to the public 3.0 experiences in socio-cultural interest such as live perform ances, tourist itineraries or museum exhibitions of archaeological or artistic nature.Our team daily researches communication solutions with the most innovative technologies such as virtual and augmented reality.